ANTIFUNGAL EVALUATION OF DICHROSTACHY cinerea (LEAVES AND STEM) EXTRACTS AGAINST SOME DERMATOPHYTES - Abdullahi, Halima Isah; Yusha'u, Muhammad (FUDMA Journal of Sciences, 2021)
This study was carried out to evaluate the antifungal efficacy of Dichrostachys cinerea extracts against some isolates of dermatophytic fungi. The powdered plant materials were extracted via soxhlet extraction technique using methanol, dichloromethane and petroleum ether as extraction solvents. The extracts were subjected to phytochemical screening for qualitative detection of plant secondary metabolites. The extracts were further tested for antifungal activity against human isolates of Microsporum canis, Trichophyton terrestre, Trichophyton mentagrophytes and Trichophyton verrucosum. The results of phytochemical screening showed the presence of some secondary metabolites including; alkaloids, tannins, saponins, glycosides and steroid. Antifungal activity testing indicated that all the extracts were active against the isolates tested with the exception of T. verrucosum. Pet ether extracts showed the least activity as reflected in the zone of inhibition (24 mm at 50 mg/ml), against the isolates compared to methanol (30 mm at 25 mg/ml) and dichloromethane (30 mm at 50 mg/ml) extracts. The findings of this study, indicated that the plant is a potential for the drug candidate for the treatment of dermatophytic diseases and support the claim for their traditional use against skin diseases